PCI complexity and cardiovascular risk in relation to high bleeding risk among patients receiving drug-eluting Stents: insight from China Fuwai PCI registry. (25th November 2020) - Wang, H.Y; Gao, R.L; Xu, B; Kirtane, A; Dou, K
Abstract: Background: The relation between complex percutaneous coronary intervention (PCI), high bleeding risk (HBR), and adverse events after coronary artery implantation of drug-eluting stents has been incompletely characterized. This study sought to investigate the ischemic and bleeding events after complex PCI including a stratification according to HBR estimated by PARIS bleeding risk score. Methods: Between January 2013 and December 2013, 10, 167 consecutive patients undergoing PCI were prospectively enrolled in Fuwai PCI Registry. Complex PCI was defined when having at least one of the following characteristics: 3 vessels treated, ≥3 stents implanted, ≥3 lesions treated, bifurcation with 2 stents implanted, total stent length >60 mm, treatment of chronic total occlusion, unprotected left main PCI, in-stent restenosis target lesion, and severely calcified lesion requiring a rotablator system. The primary ischemic endpoint was major adverse cardiovascular events (MACE) [composite of cardiac death, myocardial infarction, and definite/probable stent thrombosis], and primary bleeding endpoint was Bleeding Academic Research Consortium (BARC) type 2, 3, or 5 bleeding. Results: The median duration of follow-up was 30 months. In adjusted Cox regression analysis, patients having complex PCI procedures experienced higher risks of MACE (hazard ratio [HR]: 1.63, 95% confidence interval [CI]: 1.38–1.92; P<0.001), compared with non-complex PCI. In contrast, the risk of clinically relevant bleeding was statistically similar between the 2 groups (HR: 0.86 [0.66–1.11]; P=0.238). There was no statistical interaction between HBR (PARIS bleeding score ≥8 or <8) and complex PCI in regard to MACE (adjusted Pinteraction=0.388) and clinically relevant bleeding (adjusted Pinteraction=0.279). Conclusions: Patients who had undergone complex PCI resulted in substantially more ischemic events, without an increase in clinically relevant bleeding risk; and these associations did not seem to be modified by HBR status. More intensified antiplatelet therapy may be beneficial for patients with complex percutaneous coronary revascularization procedures. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences;National Natural Science Foundation of China